Natural phonetic tendencies and social meaning: Exploring the allophonic raising split of price and mouth on the Isles of Scilly. (4th January 2019) - Moore, Emma; Carter, Paul
Abstract: The existence of an allophonic split between raised onsets before voiceless consonants and more open onsets in other environments is well-established for the vowels in theprice lexical set. It has also been observed—less frequently—for the vowels in themouth lexical set. We provide evidence of this allophonic raising split in the English spoken on the Isles of Scilly (a group of islands off the southwest coast of England) where the pattern is more robust formouth thanprice . We propose that the allophonic raising split on Scilly is the outcome of dialect contact and natural phonetic tendencies, as observed elsewhere. However, by reflecting on the specifics of the location studied, and drawing on a perception study, we hypothesise that the trajectory of the pattern may be the consequence of the different social and regional qualities indexed bymouth andprice and the interaction of these meanings with ideologies about Scilly and its speakers.